(untitled) (Sociologisk Forskning, 1998)
Media and (popular) culture This article is a discussion of media in relation to culture and popular culture. Internationally as well as in Sweden, there has been a ‘cultural turn’ in media research, where theories and methods have been increasingly influenced by cultural studies. Of particular importance is the cultural studies’ concepts of culture as lived experience or as practices through which meaning is produced and shared between people. Meaning is expressed through different symbolic forms that in our society to a high extent are carried by media. An example is rock lyrics, a genre of mediated communication, i.e. symbolic expressions mediated by media like phonograms, radio, television or video. They are also elements of popular music, which is a part of popular culture - a phenomenon closely connected to the rise of modernity. Popular culture is defined as massproduced cultural products which are used and spread among large groups of the population and which are generally classified by the dominant taste as having little value. The article ends with an analysis inspired by cultural studies of a mediated symbolic expression: two rock texts by the famous Swedish rock artist Eva Dahlgren. The author claims that it is possible to reveal crucial traits and tendencies of the cultural context through such an analysis of the unique mediated text.